PUBLIC PARTICIPATION IN THE ADMINISTRATION OF SUBDISTRICT ADMINSTRATIVE ORGANAZATION - บุญสนอง วิชิต; เบียดนอก ชูชีพ; ชยามฤต โสมวลี; เอกธวัชกุล เกศริน; ลักขณาภิชนชัช ทัศนีย์ (Thai Interdisciplinary and Sustainability Review, 2023)
This study aims 1) to study public participation in the administration of subdistrict administrative organization and 2) to compare level of public participation in the administration of subdistrict administrative organization by personal factors. The samples were 400 people who live in Kaosai, Pichit. The data was collected using a questionnaire. The statistical methods were categorized into the descriptive such as frequency, percentage, mean, and standard deviation and inferential statistic methods was t-test, one-way ANOVA (F-test). The results showed that 1) the level of public participation in the administration of subdistrict administrative organization was moderate and 2) the differences of personal characteristics were including education, income and length of stay affect public participation in the administration of subdistrict administrative organization at the significant level of 0.05.